Increased plasma prothrombin concentration in cirrhotic patients with portal vein thrombosis and prothrombin G20210A mutation - Amitrano, Lucio; Guardascione, Maria Anna; Ames, Paul R. J.; Margaglione, Maurizio; Iannaccone, Luigi; Brancaccio, Vincenzo; Balzano, Antonio (Thrombosis and Haemostasis, 2006)
It was the aim of the present study to investigate factor II levels in liver cirrhosis (LC) patients with portal vein thrombosis (PVT) carrying the heterozygous G20210A prothrombin (PT) mutation. Plasma concentrations of factor II, VII, X, V, protein C (PC) total protein S (tPS) antithrombin (AT) and D-dimers (DD) were measured in 13 LC patients with PVT heterozygous for PT G20210A, in 13 LC patients with PVT without PT G20210A and in 13 LC controls matched by age, sex and Child-Pugh score. Crude factor II and factor II/DD ratio were highest in LC patients with PVT heterozygous for PT G20210A (p=0.03 and p=0.02 respectively). The factor II/PC ratio, expression of a procoagulant/anticoagulant imbalance was highest in the same group (p=0.0008). Plasma factor II levels are elevated in LC patients heterozygous for PT G20210A and may favour PVT.
Keywords: Liver cirrhosis; portal vein thrombosis; prothrombin